HIF2α supports pro-metastatic behavior in pheochromocytomas/paragangliomas. Issue 11 (November 2020) - Bechmann, Nicole; Moskopp, Mats Leif; Ullrich, Martin; Calsina, Bruna; Wallace, Pål William; Richter, Susan; Friedemann, Markus; Langton, Katharina; Fliedner, Stephanie M J; Timmers, Henri J L M; Nölting, Svenja; Beuschlein, Felix; et al.
Abstract : Mutations that drive the stabilization of hypoxia inducible factor 2α (HIF2α) and downstream pseudohypoxic signaling are known to predispose to the development of pheochromocytomas and paragangliomas (PPGLs). However, any role of HIF2α in predisposition to metastatic disease remains unclear. To assess such a role we combined gene-manipulations in pheochromocytoma cell lines with retrospective analyses of patient data and gene expression profiling in tumor specimens. Among 425 patients with PPGLs identified with mutations in tumor-susceptibility genes, those with tumors due to activation of pseudohypoxic pathways had a higher frequency of metastatic disease than those with tumors due to activation of kinase-signaling pathways, even without inclusion of patients with mutations in SDHB (18.6% vs 4.3% in, P < 0.0001). Three out of nine (33%) patients with gain-of-function mutations in HIF2α had metastatic disease. In cell line studies, elevated expression of HIF2α enhanced cell proliferation and led to increased migration and invasion capacity. Moreover, HIF2α expression in HIF2α-deficient cells resulted in increased cell motility, diffuse cluster formation and emergence of pseudopodia indicating changes in cell adhesion and cytoskeletal remodeling. In a mouse liver metastasis model, Hif2a enhanced the metastatic load. Transcriptomics data revealed alterations in focal adhesion and extracellular matrix–receptor interactions in HIF2α -mutated PPGLs. Our translational findings demonstrate that HIF2α supports pro-metastatic behavior in PPGLs, though other factors remain critical for subsequent transition to metastasis. We identified LAMB1 and COL4A2 as new potential therapeutic targets for HIF2α-driven PPGLs. Identified HIF2α downstream targets might open a new therapeutic window for aggressive HIF2α-expressing tumors.